2013
DOI: 10.3386/w19722
|View full text |Cite
|
Sign up to set email alerts
|

Managing the Family Firm: Evidence from CEOs at Work

Abstract: We develop a new survey instrument to codify CEOs' diaries in large samples and use it to measure the labor supply of 1,114 family and professional CEOs of manufacturing firms across six countries (Brazil, France, Germany, India, the United Kingdom and the United States). By this measure, family CEOs work 9% fewer hours relative to professional CEOs, even when we control for a wide range of CEO, firm and industry characteristics. The di↵erences in hours worked between family and professional CEOs are larger wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
54
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 41 publications
7
54
0
Order By: Relevance
“…The importance of leadership, and the extent to which CEOs contribute to company success are questions that have long been at the center of economic debate. A number of recent studies have shown that individual CEOs are key determinants of how companies are managed, and of how they perform; see, for example, Bertrand and Schoar (2003), Bennedsen et al (2007), and Bandiera, Prat and Sadun (2013). These papers also show significant heterogeneity in the management styles, skills, and even the hours worked by CEOs.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of leadership, and the extent to which CEOs contribute to company success are questions that have long been at the center of economic debate. A number of recent studies have shown that individual CEOs are key determinants of how companies are managed, and of how they perform; see, for example, Bertrand and Schoar (2003), Bennedsen et al (2007), and Bandiera, Prat and Sadun (2013). These papers also show significant heterogeneity in the management styles, skills, and even the hours worked by CEOs.…”
Section: Introductionmentioning
confidence: 99%
“…In the wake of Griffith, Redding and Van Reenen (2004) we measure the speed of technological change in a sector by the average change of R&D intensity between 1987-1993 and 1994-2007 in advanced countries. 3 We find a positive and significant correlation between the increase in R&D intensity in advanced countries and the increase in misallocation in Italian sectors. Once we account for the sectoral composition of Italian regions and firm size classes, the implied "frontier shocks" are the strongest for Northern regions and big firms, thus matching the relative increase in misallocation across geographical areas and firm sizes.…”
Section: Introductionmentioning
confidence: 60%
“…On the contrary, firms less likely to be keeping up are inefficiently large and thus over-resourced. These are the firms that have a large share 3 R&D intensity is measured as the share of R&D expenditure over value added at the sectoral level. Data are from the ANBERD database of the OECD.…”
Section: Introductionmentioning
confidence: 99%
“…For example, one study of jobs in the finance industry across four countries found an average working week of 50 hours with employees reporting that they commonly come in early or stay late in response to unpredictable events or strict deadlines (Wharton and Blair-Loy, 2006). Similarly, top level positions often involve taking responsibility for deadlines and resolving crisis situations which can require long or irregular hours making part-time or flexible hours difficult (Johns, 2013;Bandiera et al, 2014). Thus, while work-life balance policies have been designed to help women stay in the workforce and to an extent they have, they may actually serve to deepen vertical segregation because they are not able to conform to the demands of higher level positions without sacrificing time off (Hakim, 2006;Healy, 2004).…”
Section: Work-life Balancementioning
confidence: 99%